ANALISIS PERMINTAAN PEMBIAYAAN PERTANIAN SYARIAH UNTUK USAHATANI PADI DI KABUPATEN LAMPUNG TENGAH - Budi Yoko (Universitas Teuku Umar, 2016)
Capital constraints and low access to financial services from financial institutions remains a constraint for most farmers in Indonesia. Sharia Cooperative Financial Services or Koperasi Jasa Keuangan Syariah (KJKS) as one of the microfinance institutions that grow and develop in rural areas have potential to improve farmers' access to sources of capital. The objective of this study are to identify the factors that affect farmers' demand to agricultural financing sharia and to estimate realization of agricultural finance sharia for rice farming. The results of multiple linear regression model analysis, it is known that the factors that influence the demand of farmers on agricultural financing of KJKS is cost of funds and farm income. Moral hazard occurs in the realization of agricultural finance, agricultural finance obtained where farmers are not fully applied in rice farming activities.